Alter Apelles: Dürer's 1500 Self-Portrait. (20th November 2015) - Sullivan, Margaret A.
Abstract: The persistence of interpretations that view Dürer's 1500 Self-Portrait as a Christlike image in spite of the issue of blasphemy it raises is due in large part to the lack of a competing historical narrative, one that accounts for the unusual aspects of the painting without recourse to religious imagery. In this article, Dürer's motivation in creating this unprecedented painting and the strategies he used in constructing it are analyzed from the perspective of his contemporaries. In this alternative view, the humanist context is crucial, with Dürer emulating the greatest artist of the ancient world by composing the 1500 Self-Portrait in ways that accord with Apelles's art, practice, and reputation as it was transmitted through the literature of the ancient world.